Policy-Oriented Reforms and Their Consequences on MSME Performance: Evidence from Azerbaijan - Yusif, Ahmed Nadim (Bina Bangsa International Journal of Business and Management, 2022)
Small and medium companies (SMEs) are one of the most important economic elements supporting modern economies, and the Azerbaijani government has implemented measures to promote the SME sector in recent years, with the goal of reducing reliance on oil. The Republic of Azerbaijan's Small and Medium Business Development Agency, founded in 2017, is an excellent example of this strategy. The goal of this paper is to conduct a descriptive analysis of the influence of SME-friendly economic reforms on SMEs' economic performance. The article analyses the impact of SME reforms on SMEs, particularly after 2016, using data from the State Statistics Committee of the Republic of Azerbaijan to study changes and trends in macroeconomic indicators of SMEs from 2006 to 2019. The results show that the reforms are having a beneficial impact, with rising trends in terms of value addition and job creation by SMEs. Despite these encouraging achievements, Azerbaijan's percentage of SMEs in GDP and employment remains low when compared to developed countries